THE IMPORTANCE OF USING INNOVATIVE TEACHING AND TRANSLATION TECHNIQUES IN ENGLISH LANGUAGE TEACHING AND LEARNING (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article deals with the significance of innovative teaching and translation techniques in English language education, highlighting how these approaches can transform the learning experience for students.